Investigation of the prevalence of primary exercise addiction among Finnish full ironman athletes and its association with coping skills and resilience - Ahtikari, Emilia (2024)
An Ironman event imposes rigorous physical and mental demands on every participant. Athletes must undertake extensive mental and physical preparation to be adequately equipped and ready to compete in the race. Individuals executing ultra-endurance sport, such as Ironman triathletes show proneness to mental health illnesses, revealing that the sport population is not as shielded from mental health problems as previously thought. As the sport is characterized by high volume of training, problems may arise when individual creates a maladaptive relationship with exercise ultimately surpassing their individual resources. This may rise the risk of exercise addiction, thus information about the risk factors and preventative matters, is obliged. During stressful life events coping skills and resilience have been defined useful for athletes to be resistance for illness. This thesis explores the connection between exercise addiction and coping skills and resilience, among Finnish full Ironman athletes, emphasizing the importance of understanding risk factors and preventative measures. This research used a cross-sectional, quantitative, data-driven design. It included three psychometric instruments and a modified questionnaire for gathering general information, facilitating a well exploration of the chosen topic. Results showed that 12.35% were at risk for exercise addiction. Contradictory conclusions were found regarding the association of coping skills on a lower risk for exercise addiction. No association was found between resilience and the risk for exercise addiction. In a similar vein, no associations were found between exercise addiction scores and number of days per week dedicated for training or between the amount of weekly training sessions. Understanding the psychological dynamics is crucial for risk assessment and prevention of exercise addiction and in fostering a positive sports culture among ultra-endurance sports. Future research should put greater emphasis on the psychological factors at play in endurance sports for effective intervention.